2014
DOI: 10.1287/opre.2014.1264
|View full text |Cite
|
Sign up to set email alerts
|

On the Estimation of Marginal Cost

Abstract: This article proposes the estimation of marginal cost of individual firms using semiparametric and nonparametric methods. These methods have a number of appealing features when applied to cost functions. The empirical analysis uses data from a unique sample of the California electricity industry for which we observe the actual marginal cost and estimate the marginal cost from these data. We compare the actual values of marginal cost with the estimates from semiparametric and nonparametric methods, as well as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…We check the robustness of our results by using the translog model. We find some deviations in our results that are in line with the study of Delis, Iosifidi, and Tsionas (). However, our main results on the effect of foreign bank presence on bank market power are qualitatively similar.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…We check the robustness of our results by using the translog model. We find some deviations in our results that are in line with the study of Delis, Iosifidi, and Tsionas (). However, our main results on the effect of foreign bank presence on bank market power are qualitatively similar.…”
supporting
confidence: 92%
“…A popular approach has been to estimate a translog cost function and take its derivative to obtain the marginal cost. Some recent work has shown that it is possible to improve on this methodology with semiparametric or nonparametric methods that allow for more flexibility in the functional form (McAllister and McManus , Delis, Iosifidi, and Tsionas ). We follow this new literature and estimate the cost function using a partial linear smooth coefficient (PLSC) model.…”
Section: Variables and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…for small investments x i , with the prefactor c i corresponding to the initial marginal costs [28]. The occurrence of catastrophic poverty depends on the functional form of the dispersion relation close to the profitability limit, viz.…”
Section: Convex and Concave Cost Functionsmentioning
confidence: 99%
“…The GTL models are widely used in applied econometrics modeling of activities in the aggregate economy, manufacturing and service industries, and in establishments 1 [see, for example, energy (Boluk & Koc, 2010), banking (Horvath, Seidler, & Weill, 2016;Knott, Posen, & Wu, 2009), supply chain logistics (Liu, Wang, Yao, & Yue, 2016), agriculture (Kavoi, Hoag, & Prichett, 2009), health systems (Granderson, 2011;Suraratdecha & Okunade, 2006), primary healthcare (Guiffrida, Gravelle, & Sutton, 2000), general cost modeling (Delis, Iosifidi, & Tsionas, 2014), aluminum smelting (Gagne & Nappi, 2000)], information technology (Chwelos, Ramirez, Kraemer, & Melville, 2010), and others. The widespread acceptance of the GTL is rooted in (Christensen, Jorgenson, & Lau, 1973), a landmark paper.…”
Section: Generalized Translog Modelsmentioning
confidence: 99%